Investigation of effects associated with educational environment and equipment in clinical learning of speech therapy - Gerivani, Hossein; Mobaraki, Hossein; Kamali, Mohammad; Ghorbani, Ali (International Journal of Engineering and Technology, 2018)
Aim: This study aim to investigate educational environment and equipment and their effects on clinical learning of speech therapy.Investigation method: Content analysis was employed for conduct this research, for which 13 university students, 6 trainers, and 6 therapists practicing speech therapy were selected through purposive sampling. Data was collated using in-depth semi-structured interviews and also group discussion sessions and analyzed using Colaizzi method.Findings: The results of current study showed that educational environment and equipment are contributing factors to quality of clinical learning through speech therapy. Findings of the study were classified as two main concepts i.e. physical space, and equipment and software, each of which was in turn divided into smaller categories of concepts.Conclusion: The findings of the study revealed that physical space of clinical learning and use of therapeutic equipment in such spaces are contributing factors to clinical learning associated with speech therapy.Â Â